Teacher Empathy and Student Well-Being: The Mediating Role of Classroom Belongingness in the Primary Education Context - Ahmed, Rizwan (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
The purpose of the present research was to investigate the relationship between the teacher empathy (TE) with the student well-being (SW) in Pakistan primary schools. The paper also examines how the classroom belongingness (CB) is an intermediate variable that influences the connection between teacher empathy and student well-being. The sample size of 289 students in different schools in Pakistan was used to gather data. To test the hypotheses, structural equation modeling (SEM) was put into place. The findings indicated that the hypothesized model of research was upheld. Findings showed that TE had a positive impact on the sense of well being and general school experience of the students. Moreover, the feeling of CB among students increased the beneficial effects of TE on the well-being. Another effect of the study that was identified is the mediating impact of CB on the connection between TE and SW. The findings highlight the significance of TE and the establishment of inclusive supportive learning classroom settings to enhance SW within the Pakistani cultural background that is impacted by collectivist and strong inter-communal relationships. As far as the authors know, it is one of the first studies to investigate the correlations between TE, CB and SW in primary education setting in Pakistan. The findings provide more insight into the way that social-emotional teacher practices can support SW and emphasize the cultural applicability of empathy-driven education.